PHOTOGRAPHY, MEMORY AND HISTORY IN THE YEARS OF ANNIE ERNAUX - Andrade, Juscimara (Revista (Entre Parênteses), 2025)
The article examines the use of photographic descriptions in the construction of Annie Ernaux’s book, The Years (2021), winner of the 2022 Nobel Prize in Literature. It establishes a dialogue between the photographs described in the work and the historical events that marked the last six decades of the 20th century. The book narrates her personal experiences during this period through photographic descriptions that play a central role in the narrative's structure, intertwining her memories with historical events and time to create a connection between them. The analysis was based on a bibliographic review, relying on authors such as Aleida Assmann (2011), Roland Barthes (1984), and Jacques Le Goff (1990), who discuss cultural memory, the nature of photography, and the role of memory in the development of historical narratives. It investigates how the descriptions of the images evolve into visual testimonies of individual memory, thereby revealing social, political, and cultural transformations. It concludes that photography, as a document, is essential for preserving individual and collective memory, serving as a testament to the past.